Effect of venting range hood flow rate on size-resolved ultrafine particle concentrations from gas stove cooking. Issue 12 (2nd December 2018) - Sun, Liu; Wallace, Lance A.; Dobbin, Nina A.; You, Hongyu; Kulka, Ryan; Shin, Tim; St-Jean, Melissa; Aubin, Daniel; Singer, Brett C.
Abstract: Cooking is the main source of ultrafine particles (UFP) in homes. This study investigated the effect of venting range hood flow rate on size-resolved UFP concentrations from gas stove cooking. The same cooking protocol was conducted 60 times using three venting range hoods operated at six flow rates in twin research houses. Size-resolved particle (10–420 nm) concentrations were monitored using a NanoScan scanning mobility particle sizer (SMPS) from 15 min before cooking to 3 h after the cooking had stopped. Cooking increased the background total UFP number concentrations to 1.3 × 10 3 particles/cm 3 on average, with a mean exposure-relevant source strength of 1.8 × 10 12 particles/min. Total particle peak reductions ranged from 25% at the lowest fan flow rate of 36 L/s to 98% at the highest rate of 146 L/s. During the operation of a venting range hood, particle removal by deposition was less significant compared to the increasing air exchange rate driven by exhaust ventilation. Exposure to total particles due to cooking varied from 0.9 to 5.8 × 10 4 particles/cm 3 ·h, 3 h after cooking ended. Compared to the 36 L/s range hood, higher flow rates of 120 and 146 L/s reduced the first-hour post-cooking exposure by 76% and 85%, respectively. © 2018 Crown Copyright. Published with license by Taylor & Francis Group, LLC